Company Mobility in the Modern Economy - Vazhenin, Sergey G.; Vazhenina, Irina S. (Economy of Regions, 2021)
While the modern economy demonstrates an increase in company mobility, neither economists nor company managers pay due attention to this developing socio-economic phenomenon. Therefore, we analysed how new organisations enter the market of companies and old enterprises leave it after losing their viability, noting the specific features of these processes. We examined the market of companies in Russia in general and in the Federal Districts of the Russian Federation in particular. We used the data from 1 January 2001 to 1 January 2020 published in the Statistical Register of Organisations of Federal State Statistics Service (Rosstat). The research methodology includes synthesis, analysis, comparison methods, and systemic-structural approach. The obtained results showed that, since 2016, the share of officially liquidated companies in the Russian Federation and most of its regions exceeds the birth rate of organisations. This is inextricably linked to the worsening economic situation in Russia, including the business environment. We noted that privately owned companies and organisations with joint Russian and foreign ownership have the highest turnover. The average annual turnover of organisations in Russia amounted to 16.8 % in the period 2001–2019. Among the federal districts of the Russian Federation, organisations of the Siberian and Ural Federal Districts have demonstrated the greatest dynamics of the market of companies over the 19-year period (18.1 % and 17.4 %, respectively). Corresponding changes have taken place in the structure of organisations in the market of Russian companies. The share of companies providing various services has sharply increased, including transport and communication companies, and real estate organisations. New organisations with an established business reputation are mostly registered in the regions with higher competitive immunity, characterised by a favourable business environment for small- and medium-sized enterprises. The research results can be used by authorities for managing the spatial development of territories, and determining the support for certain types of business activities in a particular region or municipality.